Enhanced adhesion and electrochemical performance of Si anodes with gum arabic grafted poly(acrylic acid) as a water‐soluble binder. Issue 12 (16th June 2021) - He, Jiarong; Zhang, Lingzhi; Zhong, Haoxiang
Abstract: Gum arabic grafted poly(acrylic acid) (GA‐ g ‐PAA) is synthesized as a mechanically robust water‐soluble binder for silicon (Si) anodes in lithium‐ion batteries by graft polymerization of acrylic acid onto GA backbone via a free radical reaction. 1 H NMR and Fourier transform infrared spectroscopies and thermogravimetric analysis are systematically conducted to confirm the grafting polymerization process. GA‐ g ‐PAA with different grafting length of PAA shows enhanced adhesion strength and excellent flexibility after grafting. Optimal Si‐GA‐ g ‐8PAA electrode displays better cyclic stability, higher Coulombic efficiency and superior rate properties compared with a Si electrode with linear PAA binder. The Si‐GA‐ g ‐8PAA electrode exhibits a high electrical conductivity, low interfacial/charge transfer resistance and high lithium‐ion diffusion coefficient. GA‐ g ‐8PAA binder with grafted structure not only can maintain the mechanical and electrical integrity of the electrode, facilitating favorable electrochemical kinetics, but also assists in preserving a stable solid electrolyte interphase on Si surface upon long‐term cycling. Such a facile strategy for designing a novel grafted binder shows potential for practical application on high‐capacity anode materials with large volume change. © 2021 Society of Industrial Chemistry. Abstract : Water‐soluble GA‐ g ‐PAA is synthesized via a graft polymerization of acrylic acid on gum arabic. GA‐ g ‐PAA shows enhanced adhesion strength and excellent flexibility. Si electrode with GA‐ g ‐PAA binder exhibits excellent cyclic stability and rate capability and superior electrochemical kinetics.